Power, strategy and games economic regulation of a privatized utility. - Melville, Abigail
"This article rejects conventional `rational actor' models of economic regulation in favour of a focus on processes of resource exchange and dependence. Using a case study of Yorkshire Water it identifies the membership and structure of the regulatory arena, the resources available to regulatory actors, the `rules of the game', and the strategies adopted by regulator and regulated. It highlights the structurally privileged position of investors in water regulation and concludes that decision-making excludes customer interests; decisions are made by professional actors on the basis of co-operation and consensus; the regulator is relatively weak and depends on companies compliance to maintain its own legitimacy; and large companies have a great range of strategic options in pursuit of regulatory advantage"
Keywords: Public utilities - Great Britain; Regional water and sewage companies; Water authority; Public policy - Great Britain; Privatization - Great Britain; Water supply - Great Britain